Where black stars rise - Shammas, Nadia (A Nightfire Book, published by Tom Doherty Associates, 2022)
"Nadia Shammas and Marie Enger's Where Black Stars Rise is an eldritch horror graphic novel that explores mental illness and diaspora, set in modern-day Brooklyn. Dr. Amal Robardin, a Lebanese immigrant and a therapist in training, finds herself out of her depth when her first client, Yasmin, a schizophrenic, is visited by a nightly malevolent presence that seems all too real. Yasmin becomes obsessed with Robert Chambers' classic horror story collection The King in Yellow. Messages she finds in the book lead Yasmin to disappear, seeking answers she can't find in therapy. Amal attempts to retrace her patient's last steps-and accidentally slips through dimensions, ending up in Carcosa, realm of the King in Yellow. Determined to find her way out, Amal enlists the help of a mysterious guide. Can Amal save Yasmin? Or are they both trapped forever? "Strange is the night where black stars rise, and strange moons circle through the skies. But stranger still is lost Carcosa..." -The King in Yellow by Robert W. Chambers"--